Pelayanan Kesehatan pada Pelatihan HSSE Karyawan dan Family Gathering Karyawan serta Keluarga PT. Sinar Bumi Nabung Lampung di Wisata Pulau Tegal Mas Lampung Selatan - Riyanto, Riyanto; Wijayanti, Yoga Tri; Widiyanti, Septi (EDUPEDIA Publisher, 2023)
Essential health services are carried out in every activity, including Employee HSSE Training and Employee and Family Gathering by PT. Sinar Bumi Nabung Lampung on Tegal Mas Island Tourism, Lampung Selatan. Activities without providing health services can have fatal consequences for sudden illness and unexpected accidents. Problems encountered in activities on the beach can occur drowning and cardiac arrest or respiratory arrest. In addition, fatigue and accidents can occur at any time during the activities carried out. The purpose of community service activities is to provide preparedness for health services during activities for sudden illness or unwanted accidents. The method used is field preparation, logistics and medicines and the provision of health services for unwanted accidents or illnesses. As a result of the activity, there were 5 people injured due to collisions with rocks on the beach and 12 people who were suddenly sick could be given optimal health services. The need to take care of each participant during activities and health service readiness in various activities in the community